Molecular Mechanisms of Heat Shock Factors in Cancer - Mikael Christer Puustinen; Lea Sistonen (MDPI, 2022)
Malignant transformation is accompanied by alterations in the key cellular pathways that regulate development, metabolism, proliferation and motility as well as stress resilience. The members of the transcription factor family, called heat shock factors (HSFs), have been shown to play important roles in all of these biological processes, and in the past decade it has become evident that their activities are rewired during tumorigenesis. This review focuses on the expression patterns and functions of HSF1, HSF2, and HSF4 in specific cancer types, highlighting the mechanisms by which the regulatory functions of these transcription factors are modulated. Recently developed therapeutic approaches that target HSFs are also discussed.